2006
DOI: 10.1007/s00114-006-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Associative learning of odor with food- or blood-meal by Culex quinquefasciatus Say (Diptera: Culicidae)

Abstract: The ability of many insects to learn has been documented. However, a limited number of studies examining associative learning in medically important arthropods has been published. Investigations into the associative learning capabilities of Culex quinquefasciatus Say were conducted by adapting methods commonly used in experiments involving Hymenoptera. Male and female mosquitoes were able to learn a conditioned stimulus that consisted of an odor not normally encountered in nature (synthetic strawberry or vanil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Since Charlwood et al 's study in Papua New Guinea [6] - possibly the first study to explicitly investigate memory in a vector - more recent studies have assessed the abilities of mosquitoes to perform associative learning (see Box 1) to visual and olfactory stimuli [13, 15-18], including some studies that failed to demonstrate learning [19]. In an example demonstrating aspects of associative learning in Cx.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Since Charlwood et al 's study in Papua New Guinea [6] - possibly the first study to explicitly investigate memory in a vector - more recent studies have assessed the abilities of mosquitoes to perform associative learning (see Box 1) to visual and olfactory stimuli [13, 15-18], including some studies that failed to demonstrate learning [19]. In an example demonstrating aspects of associative learning in Cx.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…quinquefasciatus , Tomberlin et al [15] suggested that both males and females could associate odor blends (synthetic vanilla and strawberry extracts) with either a blood (females only) or a 10% sugar reward (males and females) delivered on a glass pipette coated with the odor. Interestingly, when females were trained to learn the association between the blood or sugar reward (that is, as an unconditioned stimulus [ US ]) with the vanilla or strawberry odors (that is, the conditioned stimulus [CS]), they showed higher learning performances when sugar was used as a reward than when blood was used as a reward [15]. This was unexpected, but could be attributable to the fact that the tested odors (vanilla and strawberry) could signal a floral sugar reward, rather than a blood-host.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…In wind tunnels, experiments are usually done with one insect at a time Copland 1995, Takken et al 1997), whereas in olfactometers most studies are based on the results of groups of 15 to 50 insects. Because of the possibility of learning (Alonso and SchuckPaim 2006, McCall and Eaton 2001, Tomberlin et al 2006, individual mosquitoes should not be tested more than once, and each test should be performed with naïve insects.…”
Section: Bioassay Techniques In the Laboratorymentioning
confidence: 99%
“…Feeding decisions are largely energy-state-based, so not much change there, but we would expect that resting decisions would be most affected. For this effect to hold, mosquitoes would need to make estimates of current nectar availability from inside the domicile; this might be very difficult to achieve, though it is possible that estimates could be made and retained from previous forays (see Jhumur et al, 2006;Tomberlin et al, 2006). Second, with regard to our simulations, we assumed a fixed time to locate nectar plants whereas this parameter could be further developed to include a mean and variance based upon local conditions.…”
Section: Discussionmentioning
confidence: 99%